Implementasi Metode Sima’i pada Program Tahfiz Alquran - Liliawati, Lu’ Ailu’; Ichsan, Ahmad Shofiyuddin (azkiya, 2022)
This research revealed the implementation of sima'i tahfiz Al Qur'an method during Covid-19 pandemic at MI Baiquniyyah Jejeran Bantul Yogyakarta. This research was a field research that uses descriptive qualitative methods and a case study approach. The data collection method used observation, interviews, and documentation. The data analysis method used was a qualitative method according to Sieddel. The results of this research were 1). Implementation of sima'i tahfiz Al Qur'an method during Covid-19 pandemic at MI Baiquniyyah using the teacher's technique of recording while reading letters that would be memorized by students. The order of implementation consisted of planning, implementation, and evaluation. 2). The results of the implementation of sima'i method were very effective because when studying at home, students could listen accompanied by their parents. 3). The supporting factor for the implementation of sima'i tahfiz Al Qur'an method at MI Baiquniyyah was the student factor consisting of listening skills and students' enthusiasm in memorizing. The teacher's factors consisted of clarity when reading Al Qur'an and punctuality. Parental factors consisted of parental assistance when studying. The inhibiting factors were the different ways of learning children, the lack of communication between parents and students, and the lack of communication between teachers and students.